HUBUNGAN USIA GESTASI DAN JENIS PERSALINAN DENGAN KADAR BILIRUBINEMIA PADA BAYI IKTERUS DI RSUP NTB - Syajaratuddur Faiqah (poltekkes kemenkes mataram, 2014)
Abstract: Ikterus represent one of death cause at baby, Ikterus represent the manifestasi klinis from hiperbilirubinemia. About 25 - 50% newborn baby suffer the ikterus at first week. occurence Ikterus in RSUP NTB mount from 14,91% in the year 2012, becoming 17,92% ikterus neonaturum in the year 2013. This Research Target is to know the Assosiation of age of gestasi and Labour type with the rate bilirubinemia at baby ikterus. Desain Research is analytic observasional with the approach of cross sectional, with the population of baby ikterus in RSUP NTB, this Sampel research a number of 195 baby with the total sampling technique, analyse to use the Chi-Square test.Result of research got by Age Gestasi which is a lot of is ≥ 37 week ( 66,7%), Labour type with a lot of is with the action ( 57,9%), and rate bilirubin which is a lot of is < 12 mg / dl ( 65,1%) There are relation which signifikan ( p=0,013) between age gestasi with the rate bilirubin at baby ikterus, there no relation which signifikan ( p=0,562) between labour type with the rate bilirubinemia [at baby ikterus in RSUP NTB.